Pengaruh Persepsi Kemudahan Penggunaan dan Persepsi Manfaat Terhadap Minat Menggunakan Aplikasi Canva - Wafiq Fadillah; Saida Zainurossalamia ZA (MAMEN: Jurnal Manajemen, 2023)
This study aims to analyze and explain the Effect of Perceived Ease of Use and Perceived Benefits on Interest in Using the Canva App. The independent variable in this study is Perceived Ease of Use and Perceived Benefit, while the dependent variable is Interest in Using. This research was conducted on users and not users who knew and had used the Canva application. The sample selection technique uses nonprobability  sampling with a purposive sampling method with a sample of 75 respondents. This research is quantitative. While the data obtained is in the form of primary data because data collection is carried out by data collection techniques using questionnaires. The analysis was conducted using Partial Least Square (PLS) with SmartPLS Application version 4.0.8.4. The results of this study show that: (1) Perception of Ease of Use has a positive and significant effect on Interest in Use; (2) Perceived Benefits have a positive and significant effect on Interest in Using the Canva App.  This means that the higher the perception of ease of use and the perception of benefits, the higher the interest in using.